Understanding photosynthesis in a spatial–temporal multiscale: The need for a systemic view - Neto, Milton C. Lima [UNESP]; Carvalho, Fabricio E. L.; Souza, Gustavo M.; Silveira, Joaquim A. G. (Springer Nature, 2021)
In October 2020, at the peak of the COVID-19 pandemic, a group of young Brazilian photosynthesis researchers organized the 1st Brazilian Symposium on Photosynthesis. The event was free and online, with the presence of important guest speakers from all over the world, who discussed their recent works on topics related to the future and perspectives of photosynthesis research. Summarizing the expectations of this symposium we highlighted the importance of adopting a systemic perspective for a better understanding of photosynthesis as a complex and dynamic process. Plants are modular and self-regulating presenting metabolic redundancy and functional degeneration. Among the various biological processes, photosynthesis plays a crucial role in promoting the direct conversion of light energy into carbon skeletons for support growth and productivity. In the past decades, significant advances have been made in photosynthesis at the biophysical, biochemical, and molecular levels. However, this myriad of knowledge has been insufficient to answer crucial questions, such as: how can we understand and eventually increase photosynthetic efficiency and yield in crops subjected to adverse environment related to climate-changing? We believe that a crucial limitation to the whole comprehension of photosynthesis is associated with a vastly widespread classic reductionist view. Moreover, this perspective is commonly accompanied by non-integrative, simplistic, and descriptive approaches to investigate a complex and dynamic process as photosynthesis. Herein, we propose the use of new approaches, mostly based on the Systems Theory, which certainly comes closer to the real world, such as the complex systems that the plants represent.
Keywords: Integrative approaches; Network'; Photosynthesis; Systemic Theory